Comparatively investigating the leading and trailing spark plug on the hydrogen rotary engine. (15th January 2022) - Yang, Jinxin; Meng, Hao; Ji, Changwei; Wang, Shuofeng
Highlights: Effect of Spark plug position on hydrogen rotary engine is investigated. Leading spark plug can obtain higher power and low cyclic variation. Hydrogen rotary engine's spark plug should locate the front of the minor axis. Hydrogen rotary engine has excellent emission under lean combustion. Best CA50 of hydrogen rotary engine locates between 35 and 40°CA ATDC. Abstract: As a promising power system, hydrogen-fueled Wankel rotary engine with excellent power and emission characteristic have received attention increasingly, which makes it of great interest to investigate it. To make up for blanks, this work was conducted to experimentally investigate the effect of spark plug position on the combustion and emission characteristic of hydrogen-fueled Wankel rotary engine under 1500 r/min, 66 kPa manifold absolute pressure and 1.5 excess air ratio. The results indicate that compared to the trailing spark plug, the leading spark plug is more suitable to hydrogen-fueled Wankel rotary engines, which can realize a wider ignition range, higher maximum brake torque, lower cyclic variation and better nitric oxide emission. The maximum brake torque of adopting trailing spark plug is 31.2 N·m, which is only 87% of the maximum brake torque of 36.0 N·m with adopting leading spark plug. At the maximum brake torque ignition timing, adopting leading trailing spark plug achieves lower cyclic variation and slightly higher thermal load than adopting trailing spark plug. Besides, the optimum central heat-release point of both spark plug positions locate between 35 and 40°CA after the top dead center, and that of leading spark plug is later 2°CA than that of trailing spark plug. Moreover, both spark plug positions obtained 0 nitric oxide emission at maximum brake torque ignition timing, which means that emission will not be a problem to limit the selection of spark plug position under tested conditions.